Прикладні аспекти інтенсифікації видобутку газу газоконденсатних родовищ на пізній стадії роботи - Фесенко, Юрій Леонідович; Кривуля, Сергій Вікторович; Синюк, Борис Борисович; Фик, Михайло Ілліч (Центр Європи, 2013)
The authors are offering to use an integrated methodology based on an innovative engineering solution for developing fields at the late operational stage. Essential factors are analysed, which affect the stabilisation of natural gas and gas condensate production. Examples are given of forecasted and actual increase in production of hydrocarbons with reduced well production pressures by introducing new booster compressor stations.
Applied aspects of maintaining gas production in gas condensate production field at the late operational stage
Keywords: розробка родовищ; видобуток; природний газ; газовий конденсат